Buchberger–Weispfenning theory for effective associative rings. (November 2017) - Ceria, Michela; Mora, Teo
Abstract: We present here a new approach for computing Groebner bases for bilateral modules over an effective ring. Our method is based on Weispfenning notion of restricted Groebner bases and related multiplication.